The True History of Merlin the Magician. - Lawrence-Mathers, Anne, 1953- (Yale University Press, 2012)
Merlin the Magician has remained an enthralling and curious individual since he was first introduced in the twelfth century though the pages of Geoffrey of Monmouth's Historia Regum Britanniae. But although the Merlin of literature and Arthurian myth is well known, Merlin the historical' figure and his relation to medieval magic are less familiar. In this book Anne Lawrence-Mathers explores just who he was, and what he has meant to Britain. The historical Merlin was no rough magician: he was a learned figure from the cutting edge of medieval science and adept in astrology, cosmology, prophecy and natural magic, as well as being a seer and a proto-alchemist. His powers were convincingly real-and useful, for they helped to add credibility to the 'long-lost' history of Britain which first revealed them to a European public. Merlin's prophecies reassuringly foretold Britain's path, establishing an ancient ancestral line and linking biblical prophecy with more recent times. Merlin helped to put British history into world history. Lawrence-Mathers also explores the meaning of Merlin's magic across the centuries, arguing that he embodied ancient Christian and pagan magical traditions, recreated for a medieval court and shaped to fit a new moral framework. Linking Merlin's reality and power with the culture of the Middle Ages, this remarkable book reveals the true impact of the most famous magician of all time.